Digging deeper in Shanghai: towards a 'mechanism-rich' epidemiology. (30th October 2019) - Li, Jie; Manning, Nick; Mechelli, Andrea
Abstract: Background: There are very few close-up sociological or anthropological data informing epidemiological and psychiatric research design and/or contributing to our understanding of the relationship between mental health and specific forms of urban life. Furthermore, research on the relationships between urbanicity and mental disorder has paid little attention to the global diversity of urban experience, such as in cities in China, India and Brazil. Methods: Two innovative methods can be employed to unveil the diversified urban experience of migrants in China, i.e. an ethnography-informed sociological deep surveying instrument and an ecological momentary assessment with a smartphone app. This article introduces the design and pilot survey of these new instruments towards a 'mechanism-rich' epidemiology. Results: The ethnography-informed survey instrument enabled us to include some of the issues from the ethnography and successfully 'dig deeper' into respondents' social experience. The pilot of the smartphone app serves as 'proof of principle' that we can recruit respondents in Shanghai, and that we can receive and use the data. Conclusions: Both of these pilots have demonstrated good feasibility for studying mobility, urban life and mental health. Our next steps will be to extend the Shanghai sample, to use the app in Sao Paulo and Toronto and then hopefully in India and Africa.